Quantitative Magnetic Resonance Imaging Analysis of the Relationship Between Contact Force and Left Atrial Scar Formation After Catheter Ablation of Atrial Fibrillation. (8th November 2013) - SOHNS, CHRISTIAN; KARIM, RASHED; HARRISON, JAMES; ARUJUNA, ARUNA; LINTON, NICK; SENNETT, RICHARD; LAMBERT, HENDRIK; LEO, GIOVANNI; WILLIAMS, STEVEN; RAZAVI, REZA; WRIGHT, MATT; SCHAEFFTER, TOBIAS; et al.
Left Atrial Scar Formation After Contact Force‐Guided AF Ablation Background Catheter contact force (CF) is an important determinant of radiofrequency (RF) lesion quality during pulmonary vein isolation (PVI). Late gadolinium enhancement (LGE) magnetic resonance imaging (MRI) allows good visualization of ablation lesions. Objective This study describes a new technique to examine the relationship between CF during RF delivery and LGE signal intensity (SI) following PVI. Methods Six patients underwent PVI for paroxysmal AF using a CF‐sensing catheter and following preprocedural MRI. During ablation, CF‐time integral (FTI) and position was documented for each RF application. All patients underwent repeat LGE MRI 3 months later. The LGE SIs were projected onto a MRI‐derived 3‐dimensional left atrial (LA) shell and a CF map was generated on the same shell. The entire LA surface was divided into 5 mm2 segments. Force and LGE maps were fused and compared for each 5 mm2 zone. An effective lesion was defined when MRI‐defined scar occupied >90% of a 5 mm2 analysis zone. Results Acute PVI was achieved in 100%. Two hundred sixty‐eight RF lesions were tagged on the LA shells and given a lesion‐specific FTI. Increasing FTI correlated with increased LGE SI, which was greater when the FTI was > 1, 200 gs. Below an FTI of 1, 200 gs, an increment in the FTI resulted in only a small increment in scar, whereas above 1, 200 gs an increment in the FTI resulted in a large change of scar. Conclusion There is a correlation between FTI and LGE SI in MRI following AF ablation. Real‐time FTI maps are feasible and may prevent inadequate lesion formation.